2017
DOI: 10.1007/s00114-017-1473-5
|View full text |Cite
|
Sign up to set email alerts
|

Variation in sex pheromone emission does not reflect immunocompetence but affects attractiveness of male burying beetles—a combination of laboratory and field experiments

Abstract: Life history theory predicts a trade-off between male sexual trait expression and immunocompetence. Using burying beetles, Nicrophorus vespilloides, as a model, we investigated the relationship between male immune function, sex pheromone emission, and attractiveness under field conditions. In the first experiment, we tested whether there is a positive correlation between immune capacity, sex pheromone characteristics (quantity, relative composition, and time invested in pheromone emission), and male attractive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 73 publications
2
11
1
Order By: Relevance
“…All levels of biodiversity, ranging from organisms to ecosystems, are expected to be affected by several environmental components influenced by climate change ( Parmesan 2006 , Bellard et al 2012 ). In a previous study, we found that daytime temperature affected the amount of beetles that a male was able to attract: the higher the daytime temperature was, the lower was the amount of attracted beetles ( Chemnitz et al 2017a ). In our current study, daytime temperature did not affect the amount of beetles attracted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All levels of biodiversity, ranging from organisms to ecosystems, are expected to be affected by several environmental components influenced by climate change ( Parmesan 2006 , Bellard et al 2012 ). In a previous study, we found that daytime temperature affected the amount of beetles that a male was able to attract: the higher the daytime temperature was, the lower was the amount of attracted beetles ( Chemnitz et al 2017a ). In our current study, daytime temperature did not affect the amount of beetles attracted.…”
Section: Discussionmentioning
confidence: 99%
“…In general, our experimental design ensured that a female’s mate choice was only based on a male’s long-range sex pheromone and was not affected by visual cues or contact pheromones ( Chemnitz et al 2015 , 2017a ,b). Although experimental males were all reared under the same laboratory conditions, they might still have differed in their body condition and quality, which could affect pheromone emission ( Chemnitz et al 2015 , 2017a ). As the aim of our study was to determine whether environmental parameters influenced a male’s attractiveness, irrespective of any intrinsic effects, we controlled for the latter by exposing overall six different males per plot.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A small hole was made in the parafilm to access the genital operculum of the individual, and the artificial plug was gently inserted up to the end of the atrium by lifting the operculum with straight tweezers (Fig 1B, D, F). The surface of the artificial plug was slightly roughened with sandpaper to reach a rough surface and enhance the adhesion of hemocytes to the artificial genital plugs [95-96]. This procedure does not cause any damage to the female genitalia.…”
Section: Methodsmentioning
confidence: 99%